Proceedings of the 2018 International Conference on Islamic Economics and Business (ICONIES 2018) 2019
DOI: 10.2991/iconies-18.2019.16
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Zakat Utilization Program Based on Integrated Community Development in West Bandung Regency (Case Study of Assisted Village by Rumah Zakat)

Abstract: This paper aims to determine the effectiveness of zakat utilization based on Integrated Community Development (ICD) to affect the improvement of welfare. This study not only measures the level of welfare of the community but also mustahiq community members in Mekarwangi Village after the intervention of ICD-based zakat program. Recently, this research is still infrequent; further, there is no standardized assessment tool to measure the welfare of mustahiq community. This paper used Zakat Village Index instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…Rumah Zakat's health care is manifested through free provisional health care, mobile medical services, and maternity clinics (Latief, 2010). In an effort to evenly distribute zakat , Nurhasanah, Nurzaman, and Wibisono (2018) measured the level of income among the West Java's Mekarwangi villagers and found that Rumah Zakat's ICD intervention in this village targeted a small number of households, resulting in a significant increase in their income level. Muhtada (2007) study on peasantry reported that zakat has the potential for improving the peasant's income.…”
Section: Introductionmentioning
confidence: 99%
“…Rumah Zakat's health care is manifested through free provisional health care, mobile medical services, and maternity clinics (Latief, 2010). In an effort to evenly distribute zakat , Nurhasanah, Nurzaman, and Wibisono (2018) measured the level of income among the West Java's Mekarwangi villagers and found that Rumah Zakat's ICD intervention in this village targeted a small number of households, resulting in a significant increase in their income level. Muhtada (2007) study on peasantry reported that zakat has the potential for improving the peasant's income.…”
Section: Introductionmentioning
confidence: 99%
“…Further research by Nurhasanah et al (2019) shows the effectiveness of integrated community development-based zakat utilization in influencing welfare improvement. The results indicated that the program implemented by children in the village of Mekarwangi was quite successful but did not significantly enhance community welfare.…”
Section: Kampung Zakat Programmentioning
confidence: 97%
“…Finally, the Kampung Zakat empowerment program is not only limited to the empowerment of mustahiq people but also has an impact on development (Asnaini et al, 2020;Fauzi & Huda, 2022;Nurhasanah et al, 2019;Sari et al, 2023). The next value proposition aspect priority was initiating development (0.26).…”
Section: Priority Criteriamentioning
confidence: 99%
“…Zakat efektif dalam menolong orang miskin untuk keluar dari kemiskinan yang parah, karenanya pengumpulan dan penyaluran zakat harus dijalankan dengan baik (Abdullah dkk., 2015). Zakat perlu dikelola secara bertanggung jawab dan profesional oleh setiap lembaga zakat untuk meningkatkan kesejahteraan masyarakat (Ali dkk., 2015) Efektivitas merupakan sebuah penilaian tujuan dan sasaran sebuah organisasi dalam mencapai kesuksesan, organisasi harus dapat mempertimbangkan tujuan dan mempertahankan diri dalam mengejar target (Nurhasanah, Nurzaman & Wibisono, 2019). Efektivitas dalam zakat, infak, dan sedekah dapat dilihat dari berbagai sisi salah satunya dapat dilihat dari kinerja keuangan yang dapat dilihat dari laporan keuangan lembaga pengelola zakat.…”
Section: Pendahuluanunclassified